Effect of seasonality on the leaf phenology and physiology of Byrsonima species (Malpighiaceae) - Pereira, Barbara Godinho (2023)
Introduction: Defined seasonality in savanna species can stimulate physiological responses that maximize photosynthetic metabolism and productivity. However, those physiological responses are also linked to the phenological status of the whole plant, including leaf phenophases. Objective: To study how physiological traits influence phenophase timing among congeneric and co-occurring savanna species. Methods: We evaluated the leaf phenology and physiological traits of populations of Byrsonima intermedia, B. coccolobifolia, and B. verbascifolia. Physiological measurements were performed at the onset of the dry and rainy seasons and again late in the season. Results: B. intermedia and B. coccolobifolia were classified as brevideciduous and B. verbascifolia as evergreen. The maximum quantum yield for B. intermedia and B. coccolobifolia were lowest during the dry season. At the onset of the dry period, the highest chloroplastidic pigment levels were observed, which decreased as the season advanced, total chlorophyll/carotenoid ratios were lowest, and carotenoid contents were highest. We detected low starch content values at the start of the rainy season, coinciding with the resumption of plant growth. Two months into this season, the leaves were at their peak structural and functional maturity, with high water-soluble polysaccharide values and photosynthetic rates, and were storing large amounts of starch. Conclusions: Physiological and leaf phenological strategies of the Byrsonima species were related to drought resistance and acclimatization to the seasonality of savanna water resources. The oscillations of the parameters quantified during the year indicated a strong relationship with water seasonality and with the phenological status of the leaves. Objective: We studied how physiological traits, and not only seasonality, influence phenophase timing among congeneric and co-occurring savanna species. Methods: We followed the leaf phenologies and physiological traits of populations of Byrsonima intermedia, B. coccolobifolia, and B. verbascifolia native to the Brazilian savanna. Analyses of specific leaf mass, relative water content, leaf phenology, leaf carbohydrate content, chloroplastidic pigments, and photosynthetic efficiency were performed at different times during both the dry and rainy seasons. Physiological measurements were performed at the onset of the dry season and again late in that season, as well as at the onset of the rainy season and again late in the rainy season.   Results: Byrsonima intermedia and B. coccolobifolia were classified here as brevideciduous and B. verbascifolia as evergreen. Few variations in chlorophyll a fluorescence values were detected over the full year, with the lowest maximum quantum yield values (Fv/Fm) for B. intermedia and B. coccolobifolia occurring during the dry season. The deciduous species (B. verbascifolia) evidenced higher photosynthetic yields during periods of abundant water availability, mainly after its complete recovery after the start of the prolonged rainy period.  The highest chloroplastidic pigment levels were observed at the onset of the dry period, although chlorophyll levels decreased as the dry season advanced. The lowest total chlorophyll/carotenoid ratios and the highest carotenoid contents observed at the onset of the dry season indicated that Byrsonima plants were still investing in mechanisms of photoprotection and the dissipation of excess energy from their photosynthetic systems even under water deficit conditions. We detected low starch content values at the onset of the rainy season, which coincides with the resumption of plant growth. At two months into the rainy season, the leaves were at their peak structural and functional maturity, exhibiting high water-soluble polysaccharide values and high photosynthetic rates, and were storing large amounts of starch. Conclusions: Our data evidenced that the physiological and foliar phenological strategies of the Byrsonima species studied here were related to drought resistance and to acclimatization to the seasonality of savanna water resources. The oscillations of the parameters quantified during the year in the three studied species indicated not only a strong relationship with water seasonality, but also with the phenological statuses of the leaves.